2011
DOI: 10.1038/ejhg.2011.204
|View full text |Cite
|
Sign up to set email alerts
|

A multi-exon deletion within WWOX is associated with a 46,XY disorder of sex development

Abstract: Disorders of sex development (DSD) are congenital conditions where chromosomal, gonad or genital development is atypical. In a significant proportion of 46,XY DSD cases it is not possible to identify a causative mutation, making genetic counseling difficult and potentially hindering optimal treatment. Here, we describe the analysis of a 46,XY DSD patient that presented at birth with ambiguous genitalia. Histological analysis of the surgically removed gonads showed bilateral undifferentiated gonadal tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
0
37
0
2
Order By: Relevance
“…Notably, the two 1-Mb windows that exhibit the highest maternal mutation rates are spanned by one large gene each, CSMD1 and WWOX (Supplementary Tables 21-23). WWOX is at a well-known fragile site in the genome 13 and is known to be involved in human gonad development 14 .…”
mentioning
confidence: 99%
“…Notably, the two 1-Mb windows that exhibit the highest maternal mutation rates are spanned by one large gene each, CSMD1 and WWOX (Supplementary Tables 21-23). WWOX is at a well-known fragile site in the genome 13 and is known to be involved in human gonad development 14 .…”
mentioning
confidence: 99%
“…Indeed, CNV arrays and MLPA are often used sequentially; MLPA is frequently utilized to confirm CNV array results, determine the mode of inheritance, and screen patient cohorts for known CNVs which in turn are then fine-mapped using CNV arrays [White et al, , 2012Kim et al, 2015;Ohnesorg et al, 2017]. MLPA can also be used to detect CNVs of single exons in genes of interest [Barbaro et al, 2011]; however, due to the expense of CGD, complete gonadal dysgenesis; GD, gonadal dysgenesis; OT, ovotesticular DSD the probes, this would only be cost-effective if large cohorts were screened for particular well-known candidate genes.…”
Section: Cnv Arrays and Mlpamentioning
confidence: 99%
“…These smaller-scale rearrangements are more often detected using high density CGH and microarrays that are designed to have targets at the resolution of exons [Harrison et al, 2014]. For example, White et al [2012] identified a deletion in the WWOX gene affecting exons 6-8, while Ledig et al [2012] found a deletion of exons 3 and 4 in the DMRT1 gene. Other groups have also utilized specific MLPA probes to increase the density of their CNV analysis by focusing on each individual exon to increase the resolution [Barbaro et al, 2011].…”
Section: Cnvs Affecting Coding Sequences Of Dsd Genesmentioning
confidence: 99%
“…7 In addition, a probable regulatory element lying downstream of the GATA4 gene was identified when a 35 kb deletion was detected in a person with 46,XY complete gonadal dysgenesis. 17 Similarly, in those with 46,XY DSD, microarray analysis detected an intragenic deletion of WWOX 18 and a deletion at least 42 kb upstream of the DMRT1 gene. 19 In fact, array analyses have now identified many DNA duplications and deletions in people with DSD, several of which are located close to known sex development genes and are suspected to have caused disruption of gene regulatory regions.…”
mentioning
confidence: 97%